Dampak Pandemik Covid-19 terhadap Pengunjung dan Pendapatan Masyarakat Pesisir Sektor Pariwisata Pulau Bokori Kecamatan Soropia Kabupaten Konawe - Uswatun Nisa; Haji Saediman; Samsul Alam Fyka (Jurnal Ilmiah Membangun Desa dan Pertanian, 2022)
This study aims to determine the impact of the Covid-19 pandemic on visitors and the income of coastal communities in the tourism sector of Bokori Island. The research was conducted on Bokori Island, Soropia District, Konawe Regency. The research location was determined purposively, considering that Bokori Island is one of the tourist destinations affected by the Covid-19 pandemic. The sample in this research is 50 people who work in the tourism sector. This research was conducted from October to December 2021. The variables used in this study were the number of visitors and income. The data were analyzed by qualitative descriptive based on the results of the scoring of each variable and the paired sample t-Test. The results showed that the impact of the Covid-19 pandemic on the variable number of visitors was in the medium category and the income variable was in the high category. This is also evidenced by the results of the t-test analysis, which shows that there was a significant difference before and during the Covid-19 pandemic in people's incomes, which means that the Covid-19 pandemic had an impact on the number of visitors and the income of coastal communities in the tourism sector of Bokori Island.